SISTEM PAKAR IDENTIFIKASI PANEN BUAH NANAS MENGGUNAKAN METODE BACKWARD CHAINING BERBASIS ANDROID - Machudor Yusman; Bambang Hermanto; Indra Wijaya (Jurnal Pepadun, 2021)
This study aims to create an expert system based on android mobile device platform that can analyze the harvest period of pineapple plants based on the source of expert knowledge. This study uses 4 main variables namely Seed Origin, Planting Age, Etherel (Carbit) and Percentage of Maturity. In addition this identification system provides features for sources of knowledge in the cultivation of pineapple plants including ways of cultivation and obstacles that can interfere with the growth of these plants. The identification system uses the Backward Chaining inference method that determines the main conclusions in the rules and then determines supporting hypotheses that refer to these conclusions. System functional testing uses the Equivalence Partitioning method in the functional testing scenario. Testing accuracy using 10 random test cases then validated by an expert. From the results of testing the accuracy of using 10 test-cases obtained 80% accuracy results so that the results of the identification of the system are categorized well in determining the harvest period of pineapple.